Pancasila as a Paradigm of Economic Development in Indonesia - Wowon Winarsih; Mariatul Ulpa; Madsuki Asbari (Journal of Information Systems and Management (JISMA), 2022)
This article aims to find out the concept of Pancasila regarding Economics in Indonesia by examining Pancasila as Development. Pancasila as a paradigm means that Pancasila is a value system that is used as a basic framework, a framework of ways, and at the same time a framework of direction/goals for a nation. . In economic development, the government must be based on Pancasila. With a people's economic footing, economic policy must be aimed as much as possible for the prosperity of the people. In accordance with the Pancasila Paradigm in economic development, the economic system must be based on divine morality and humanity. It aims to prosper the people as a whole. Economic development must be able to avoid monopoly and free competition which will later provide great benefits to those who are strong in the economic field. Meanwhile, small entrepreneurs will be disadvantaged by the existence of a system of free competition in the economy.